Effect of Preparation Conditions on the Catalytic Activity of CuMnOx Catalysts for CO Oxidation - Subhashish Dey; Ganesh Chandra Dhal; Devendra Mohan; Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The hopcalite (CuMnOx) catalyst is a well-known catalyst for oxidation of CO at ambient temperature. It has prepared by co-precipitation method and the preparation parameters were like Copper/Manganese (Cu:Mn) molar ratios, drying temperature, drying time, calcination temperature and calcination time has an influence on activity of the resultant catalyst. The activity of the catalyst was measured in flowing air calcinations (FAC) conditions. The reaction temperature was increased from ambient to a higher value at which complete oxidation of CO was achieved. The particle size, weight of catalyst and CO flow rate in the air were also influenced by the activity of the catalyst for CO oxidation. The characterizations of the catalysts were done by several techniques like XRD, FTIR, BET, SEM-EDX and XPS. These results were interpreted in terms of the structure of the active catalyst. The main aim of this paper was to identify the optimum preparation conditions of CuMnOx catalyst with respect to the performance of catalyst for CO oxidation.